2019
DOI: 10.1111/hiv.12714
|View full text |Cite
|
Sign up to set email alerts
|

Depression, lifestyle factors and cognitive function in people living with HIV and comparable HIV‐negative controls

Abstract: Objectives We investigated whether differences in cognitive performance between people living with HIV ( PLWH ) and comparable HIV ‐negative people were mediated or moderated by depressive symptoms and lifestyle factors. Methods A cross‐sectional study of 637 ‘older’ PLWH aged ≥ 50 years, 340 ‘younger’ PLWH aged < 50 years and 276 demogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 45 publications
(62 reference statements)
2
18
1
1
Order By: Relevance
“…Eleven percent of HIV-positive patients reported moderate or severe depressive symptoms when measured using the PHQ-9 questionnaire. Previous studies utilising the PHQ-9 questionnaire have reported higher prevalences of depression among HIV-positive patients compared to our study, ranging from 14.5 to 27% [29][30][31]. Sociodemographic characteristics of our patients may in part explain the disparities in findings.…”
Section: Discussioncontrasting
confidence: 73%
“…Eleven percent of HIV-positive patients reported moderate or severe depressive symptoms when measured using the PHQ-9 questionnaire. Previous studies utilising the PHQ-9 questionnaire have reported higher prevalences of depression among HIV-positive patients compared to our study, ranging from 14.5 to 27% [29][30][31]. Sociodemographic characteristics of our patients may in part explain the disparities in findings.…”
Section: Discussioncontrasting
confidence: 73%
“…The clinical relevance of seeking to ‘diagnose’ ‘asymptomatic’ CI has been called into question as wasteful of resources and needlessly worrying to patients. Recent findings have shown that ANI is predictive of further cognitive decline [42] but the main moderators of these changes are common to all, including older age, cardiovascular risk factors (diabetes, hypertension, smoking), presence of depression and other health comorbidities [42,43,44]. Medication treatment strategies for CI have generally proved disappointing, within the clinic we modified cART regimens only due to patient complaint of side effects (and would have modified if presence of CSF HIV RNA was detected); besides this little recommendation or indeed clarity of evidence exists.…”
Section: Discussionmentioning
confidence: 99%
“…Interventions addressing cardiovascular risk factors and mental wellbeing appear to be of value [42,44]. At the clinic we offer patients informal advice on lifestyle (e.g., diet, exercise, sleep hygiene, drugs/alcohol intake), mental health management, adherence to cART and cognitive strategies, along with recommendations to their GP on the control of CVD risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…We calculated z -scores for individual TOVA variables and Cogstate subtests using the HIV-negative cohort as the reference sample. We then calculated global scores of executive function, speed of processing, and central auditory scores from the z -scores using an approach similar to those proposed by Kamminga et al [ 48 ] and De Francesco et al [ 52 ]. These global scores allowed us to better understand the key domains of cognition, executive function, and speed of processing.…”
Section: Methodsmentioning
confidence: 99%